Flowsheet Development and Modelling of Hydrogen Production from Empty Fruit Bunch (EFB) via Steam Gasification - Inayat, Abrar (2010)
Due to the availability of agricultural land and significant production of palm oil in Malaysia, there is abundance of biomass in the form of agricultural wastes. This work reports a mathematical model for the flowsheet developed for hydrogen production from empty fruit bunch from oil palm via steam gasification with in-situ carbon dioxide capture by CaO as sorbent. The flowsheet model incorporates the chemical reaction kinetics, mass and energy balances calculations. Parameter analysis on the influence of the temperature, steam/biomass and sorbent/biomass ratios are performed. It is predicted that more than 70 mole% hydrogen can be produced at 1150 K. In addition, CO2 are predicted to be fully absorbed from the system at sorbent/biomass ratio of 2.0. It is observed that the thermodynamic efficiency of the gasifier increases with temperature reaching a maximum efficiency of 84% at steam/biomass ratio of 2.0. It is shown that by using CaO as the sorbent in the gasifier, the efficiency can be increased by 10% compared to the conventional gasification method.